2009
DOI: 10.1111/j.1471-4159.2009.06338.x
|View full text |Cite
|
Sign up to set email alerts
|

eNOS gene deletion restores blood‐brain barrier integrity and attenuates neurodegeneration in the thiamine‐deficient mouse brain

Abstract: Wernicke's encephalopathy is a cerebral disorder caused by thiamine (vitamin B 1 ) deficiency (TD). Neuropathologic consequences of TD include region-selective neuronal cell loss and blood-brain barrier (BBB) breakdown. Early increased expression of the endothelial isoform of nitric oxide synthase (eNOS) occurs selectively in vulnerable brain regions in TD. We hypothesize that region-selective eNOS induction in TD leads to altered expression of tight junction proteins and BBB breakdown. In order to address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In rats brain, thiamin deficiency increased the endothelial nitric oxide synthase (eNOS) expression level [21]. Moreover, Beauchesne et al [22] demonstrated that eNOS affected the expression of ZO-1 and occludin in the medial thalamus of mice. The above information suggesting that thiamin may have effect on TJs in fish, which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In rats brain, thiamin deficiency increased the endothelial nitric oxide synthase (eNOS) expression level [21]. Moreover, Beauchesne et al [22] demonstrated that eNOS affected the expression of ZO-1 and occludin in the medial thalamus of mice. The above information suggesting that thiamin may have effect on TJs in fish, which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional eNOS impairs endotheliummediated relaxation and promotes vascular dysfunction and changes in its hemodynamics. In addition, the generation of oxidative stress triggered by eNOS uncoupling causes instability of the BBB steady-state (Beauchesne et al, 2009;F€ orstermann and Münzel, 2006;F€ orstermann and Li, 2011;Santhanam et al, 2012). The present data revealed transient eNOS uncoupling evidenced by a high rate of eNOS monomers occurring during early stages of severe PNV intoxication.…”
Section: Enos Uncouplingmentioning
confidence: 49%
“…In the brain, the proper functioning of the eNOS/NO system accounts for the microenvironment homeostasis needed for normal operative neuron and glial cells; NO produced by eNOS plays a key role in hemodynamics by regulating blood flow and blood pressure through the control of vasodilation and vascular resistance, platelet adhesion and aggregation, and leukocyte-to-endothelium interaction. A number of pathological settings disturb such nitrergic control, resulting in endothelial and vascular dysfunction (Iadecola, 1997; see Atochin and Huang, 2010), the incapacity of normal synthesis of eNOS derived-NO has been associated with enhanced production of reactive oxygen species, disruption of endogenous control of eNOs inhibitors, effect on BBB and NVu functioning and worsening of pathological conditions (Toda et al, 2010;F€ orstermann and Münzel, 2006;Beauchesne et al, 2009;F€ orstermann and Li, 2011;Santhanam et al, 2012). eNOS dimerization is a mandatory condition for the calciumdependent catalytic activity of the enzyme (Persechini et al, 2013), and eNOS uncoupling resulting from increased monomerization, leads to a decline in NO bioavailability and enhanced production of superoxide (Domenico, 2004;Masano et al, 2008;Münzel et al, 2005;Sabri et al, 2011;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Exendin-4, which is an analog of glucagon-like peptide 1 (GLP-1), significantly attenuates the loss of SN neurons and the striatal dopaminergic fibers in the MPTP-induced PD model, and inhibits the expression of MMP-3 [122]. MMP-9 has also been shown to be upregulated in the TD mouse brain [68,123]. Thiamine prevents diabetes-induced cardiac fibrosis and decreases MMP-2 activity in the heart of diabetic rats [124].…”
Section: Non-genomic Role Of Thiamine In Parkinson's Diseasementioning
confidence: 99%